2001
DOI: 10.1109/20.911793
|View full text |Cite
|
Sign up to set email alerts
|

Effect of electromagnetic launch on armature/sabot discard

Abstract: This paper presents the validation of a sabot discard model, developed at the Institute for Advanced Technology (IAT), for predicting armature/sabot separation, and quantifies the effect of electromagnetic launch on sabot discard as well as on the sub-projectile. The experimental data used to validate the model were obtained at the Army Research Laboratory (ARL) Transonic Experimental Facility at Aberdeen Proving Ground, MD. Five shots were conducted at a nominal velocity of 1350 m/s and armature/sabot petal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…They showed that the residual current in the sabot delays the separation in a 1100 m∕s launch. Erengil [16], Erengil and Zielinski [17], and Erengil [18] introduced a sabot separation model based on flowfields around a projectile/sabot, which divides the separation into four stages by the sabot angle and displacement from the projectile.…”
mentioning
confidence: 99%
“…They showed that the residual current in the sabot delays the separation in a 1100 m∕s launch. Erengil [16], Erengil and Zielinski [17], and Erengil [18] introduced a sabot separation model based on flowfields around a projectile/sabot, which divides the separation into four stages by the sabot angle and displacement from the projectile.…”
mentioning
confidence: 99%